Liability of A Notary in Making The Deed of Minutes of General Meeting of Shareholders in A Closed Limited Company Conducted Through Media Teleconference - Aslan Noor; Avelino William Nugraha; Purwa Surya Nugraha; Ferdinand Septiano; Bimo Lagar Sakti (NOTARIIL Jurnal Kenotariatan, 2026)
This study discusses the responsibility of the Notary in making the deed of the Minutes of the General Meeting of Shareholders and the legal consequences of the deed of the Minutes of the General Meeting of Shareholders in a Limited Company which is carried out through teleconference media. There is a conflict of norms between the provisions of Article 77 paragraph (4) of the Company Law which in essence states the minutes of the General Meeting of Shareholders via Teleconference must be approved and signed by all participants of the General Meeting of Shareholders with the provisions of Article 90 paragraph (2) of the Company Law which essentially states the minutes of the General Meeting of Shareholders. Shares in the form of a notarial deed are not required to be signed by the participants of the GMS. The purpose of this study is to analyze the responsibilities of a Notary in the Making of the Minutes of the General Meeting of Shareholders and the legal consequences of the deed of the Minutes of the General Meeting of Shareholders via teleconference. The method used is the normative law research method. Sources of legal materials are primary legal sources in the form of laws and regulations, secondary sources of legal materials in the form of books, journals, scientific documentation and tertiary legal sources in the form of large Indonesian language dictionaries and the internet. The theoretical basis used is the theory of authority, the theory of legal responsibility, the theory of legal benefit and the theory of legal certainty. The results of the study indicate that if there is an error from the Notary in making the deed of the Minutes of the General Meeting of Shareholders via teleconference, the Notary has civil, criminal and administrative responsibilities and the legal consequences are the cancellation of the deed. So, a Notary must pay close attention to the provisions of the relevant laws and regulations to avoid legal problems and stricter provisions are needed regarding the procedure for making a deed of the Minutes of the General Meeting of Shareholders in a Limited Company by teleconference.